Trace analysis of amines in cheese serum with liquid chromatographic potentiometric detection by using amine-selective electrode - Aydin, Rukiye; Asan, Adem; Attar, Azade; Isildak, Ibrahim (ELSEVIER, 2019)
A trace quantification liquid chromatographic-potentiometric method for the determination of amines in cheese serum is described. An all solid-state contact polyvinyl chloride membrane amine-selective electrode was prepared and used as a detector in a low-dead volume flow through detection cell. Potentiometric performance characteristics of the proposed electrodes were then examined. A slope of 52.4 +/- 3.8 mV per decade toward amines was received at the concentration range of 1.0 x 10(-2)-8.0 x 10(-6) M (r(2) = 0.99) under dynamic conditions. Six amine compounds were separated, with a good resolution in the chromatographic system by using acetonitrile-methane sulfonic acid mobile phase gradient at the flow-rate of 1 mL min(-1) in 30 min. The potentiometric detector was successfully applied to the analysis of amines in cheese serum samples. The relative standard deviations were ranged from 2.2% to 4.0% and recoveries were ranged from 88% to 101% for the determination. The average concentrations of ethylamine, butylamine and hexylamine in cheese serum samples calculated were 6.46, 4.51 and 8.37 mu g L-1 respectively. (C) 2016 The Authors. Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Amine-selective electrodes; Amine analysis; Potentiometric detection; High performance liquid chromatography; BIOGENIC-AMINES; ALIPHATIC-AMINES; DERIVATIZATION; DRUGS; Chemistry